DYSLIPIDEMIA AMONG THE ELDERLY IN SLUMS OF WEST DELHI - Gonmei, Zaozianlungliu; Dwivedi, Supriya; Toteja, Gurudayal Singh; Singh, Karuna; VIKRAM, NAVALKISHORE; Bansal, Priyanka Gupta; Rathore, Suman (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to assess the prevalence of dyslipidemia among the elderly in slums of West Delhi. Methods: A cross-sectional study was carried out in slums of West Delhi covering a total of 234 elderly aged 60 and above. 5 ml blood was collected from 103 elderly and was analyzed for serum total cholesterol, triglyceride, high-density lipoprotein (HDL) cholesterol, and low-density lipoprotein (LDL) cholesterol by enzymatic method using fully automatic analyzer (Roche Hitachi-902). Dyslipidemia was defined using the National Cholesterol Education Program, ATP-III guidelines. Results: The overall prevalence of high cholesterol (≥200 mg/dl), high triglyceride (≥150 mg/dl), low HDL cholesterol (male - <40 mg/dl; female - <50 mg/dl), and high LDL cholesterol (≥130 mg/dl) was 20.39%, 45.63%, 64.08%, and 17.31%, respectively. Conclusion: Low HDL cholesterol and high triglyceride were the most form of dyslipidemia among the elderly. Awareness on dietary and lifestyle modification for management of dyslipidemia needs to be imparted.